2003
DOI: 10.1136/oem.60.9.689
|View full text |Cite
|
Sign up to set email alerts
|

Driving impairment due to sleepiness is exacerbated by low alcohol intake

Abstract: Aims: To assess whether low blood alcohol concentrations (BACs), at around half the UK legal driving limit, and undetectable by police roadside breathalysers, further impair driving already affected by sleepiness, particularly in young men, who are the most "at risk" group of drivers for having sleep related crashes. Methods: Twelve healthy young men drove for two hours in the afternoon, in an instrumented car on a simulated motorway. In a repeated measures, counterbalanced design, they were given alcohol or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 15 publications
(15 reference statements)
4
60
1
5
Order By: Relevance
“…The adjustment and quality of the cluster model allow to support the clear difference in terms of these variables between professional drivers who have (or not) the habit of regularly drinking alcohol, in accordance to which has been suggested in several studies assessing the increased risk of misbehaviors and/or accidents at the wheel based on this behavior [1][2][3][4][5][6][7]43,77]. Furthermore, obtained differences in terms of Job Strain between drivers in both clusters (i.e., higher Job Strain rates for participants in cluster number 1) result consistent to other empirical research documenting the critical relationships existing between: a) job stress and both addressed addictive behaviors [34, 78,79], b) job stress and traffic accidents [49,80,81], and c) addictive behaviors such as alcohol consumption, lifestyle factors and safety outcomes [81,82].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The adjustment and quality of the cluster model allow to support the clear difference in terms of these variables between professional drivers who have (or not) the habit of regularly drinking alcohol, in accordance to which has been suggested in several studies assessing the increased risk of misbehaviors and/or accidents at the wheel based on this behavior [1][2][3][4][5][6][7]43,77]. Furthermore, obtained differences in terms of Job Strain between drivers in both clusters (i.e., higher Job Strain rates for participants in cluster number 1) result consistent to other empirical research documenting the critical relationships existing between: a) job stress and both addressed addictive behaviors [34, 78,79], b) job stress and traffic accidents [49,80,81], and c) addictive behaviors such as alcohol consumption, lifestyle factors and safety outcomes [81,82].…”
Section: Discussionmentioning
confidence: 52%
“…According to Seppala et al [3], the association of a growing crash risk linked to the increasing of blood alcohol levels is enough documented, i.e., even at low blood alcohol levels (<0.05 g/dL), an increased crash risk is to be expected [4,5], mostly when there are other risk factors present, such as sleep decreasing or sleep systematic disorders [6,7], fatigue [8][9][10], stress [11][12][13][14], mood disorders [15,16] and/or different types of drugs [17], which tend to increase the risk even more.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this the average number of line crossings per segment (4 km road driven) was calculated. Line crossings is a measure that is as close as we can come to critical situations and commonly used [22,23]. The reason left crossing were selected was based on the fact that the majority of departures were to the left.…”
Section: Measures and Data Structurementioning
confidence: 99%
“…Driving tests on a closed-circuit showed that the effects of alcohol (blood alcohol concentration = 0.089%) on driving performance were comparable to those of sleep deprivation (17). The impairing effects of alcohol on simulated driving have ben shown to be exacerbated in sleepy drivers (18). Another study quantified this impairment, showing that after 18.5 and 21 h of wakefulness, driving impairment in a simulator was comparable to that observed in drivers with blood alcohol concentrations of 0.05 and 0.08%, respectively (19).…”
Section: Alcoholmentioning
confidence: 90%